Rehabilitation of Degraded Dry Lands of Indian Arid Zone through Direct Seeding - Singh, G.; Rathod, T. R. (Indian Forester, 2006)
A field study was carried out with the aim to monitor the growth and performance of Azadirachta indica and Colophospermum mopane grown by direct seeding in rainfed condition. Half kg fruits of each species were directly broadcast in deep ploughed 300 m 2 plots. Seed germination, survival, height, collar diameter, number of branches and leaves were recorded. Root length and biomass partitioning was recorded at 9 months of age. Soil water content was recorded to observe its relation with seedling performance. Germination percent of A. indica and C. mopane was 53.9 and 94.2 in July 2001 with respective population of 27500 and 30100 seedlings ha-1 . Survival in July 2002 was 1.2 and 9.7%, respectively. Growth was significantly (P<0.05) high in C. mopane. At the age of 9 months, root of C. mopane seedligns was more than two fold larger as compared to that of A. indica. Shoot and root dry biomass produced by C. mopane was 5.4 and 6.6 fold higher than the respective biomass of A. indica seedlings. Biomass allocation was high in roots in both species and it was at the expense of leaves in A. indica and stem in C. mopane. High survival in C. mopane seedlings was due to their deep rooting behaviour thereby extracting water from the deeper soil layers as compared to A. indica, the roots of which confined in top 70 cm layer. Conclusively, C. mopane had greater adaptability to the dry areas and could easily be raised by direct seeding.